The swallows : a novel - Lutz, Lisa (Ballantine Books, 2019)
A new teacher at a New England prep school ignites a gender war--with deadly consequences--in a provocative novel from the bestselling author of The Passenger and the Spellman Files series. What do you love? What do you hate? What do you want? It starts with this simple writing prompt from Alex Witt, Stonebridge Academy's new creative writing teacher. When the students' answers raise disturbing questions of their own, Ms. Witt knows there's more going on the school than the faculty wants to see. She soon learns about The Ten--the students at the top of the school's social hierarchy--as well as their connection to something called The Darkroom. Ms. Witt can't remain a passive observer. She finds the few girls who've started to question the school's "boys will be boys" attitude and incites a resistance that quickly becomes a movement. But just as it gains momentum, she also attracts the attention of an unknown enemy who knows a little too much about her--including what brought her to Stonebridge in the first place. Meanwhile, Gemma, a defiant senior, has been plotting her attack for years, waiting for the right moment. Shy loner Norman hates his role in the Darkroom, but can't find the courage to fight back until he makes an unlikely alliance. And then there's Finn Ford, an English teacher with a shady reputation who keeps one eye on his literary ambitions and one on Ms. Witt. As the school's secrets begin to trickle out, a boys-versus-girls skirmish turns into an all-out war, with deeply personal--and potentially fatal--consequences for everyone involved. Lisa Lutz's blistering, timely tale shows us what can happen when silence wins out over decency for too long--and why the scariest threat of all might be the idea that sooner or later, girls will be girls.